Ask a question

9t+6 ÷t(t+3) = 7÷t +3

Solve proportion



1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Andrew R. | Patient and Knowledgeable Math TutorPatient and Knowledgeable Math Tutor
4.7 4.7 (26 lesson ratings) (26)

9t+6/t(t+3) = 7/(t+3)

(9t+6)(t+3)=7t(t+3)      (Cross multiply the proportion)

9t+6=7t         (divide (t+3) from both sides)

2t+6=0              (subtract 7t from both sides)

2t=-6          (subtract 6 from both sides to solve for t)

t=-3          (answer)

However, notice that when t=-3 the proportion is undefined on both sides, because when t=-3 the denominator is 0.